Corporate communications and branded content on Facebook: A study of the official accounts of Peruvian universities - Atarama-Rojas, Tomás (2020)
This research explores the use of Facebook as a corporate communications channel of Peruvian universities. The study aims to find out which communication elements generate the greatest interaction. To this end, content analysis is carried out, which allows to detect communicative actions, formats, themes and emotional links that lead to greater participation of audiences in this social network. This methodology is complemented by a qualitative analysis of the most relevant posts. Results show that content valued most by the public seeks to educate and inspire with the results of research and scientific innovation and through audiovisual formats, appealing to a sense of pride of the community.